1990
DOI: 10.1159/000200391
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin Receptor Antagonist Loxiglumide: Influence on Bilio-Pancreatic Secretion and Gastrointestinal Hormones in Man

Abstract: We characterized the effect of the specific cholecystokinin (CCK) receptor antagonist loxiglumide (CR 1505) on gallbladder contraction, pancreatic enzyme output and plasma CCK concentrations determined by radioimmunoassay and bioassay. Gallbladder emptying and bilirubin output in response to the intraduodenal administration of a mixed liquid meal were completely inhibited by an intravenous infusion of loxiglumide (10 mg/ kg/h). In contrast, meal-stimulated pancreatic enzyme secretion was diminished by only 30–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It was also observed during infusion of the CCK analogue cerulein [22]. When CCK-8 was infused, antagonist treat ment slightly increased plasma CCK concen trations in one study [3], but had no efect in further studies [23,24].…”
Section: Discussionmentioning
confidence: 91%
“…It was also observed during infusion of the CCK analogue cerulein [22]. When CCK-8 was infused, antagonist treat ment slightly increased plasma CCK concen trations in one study [3], but had no efect in further studies [23,24].…”
Section: Discussionmentioning
confidence: 91%
“…This finding provides support for the hypothesis that CCK release in response to a meal ; feedback-controlled by bile acids, as has been sho-7-In dogs and humans [50,5 11. Since CCK-receptor antago-nists almost completely inhibit postprandial gallbladder emptying and bile secretion into the duodenum [16][17][18][23][24][25][26], it is suggested that CCK release in humans is regulated via negative feedback control by bile acids: decreasing intraduodenal concentrations of bile acids stimulate postprandial CCK secretion. Feedback regulation of CCK release by intraluminal protease activity is probably of minor importance.…”
Section: Discussionmentioning
confidence: 99%
“…Ten healthy male volunteers (aged [22][23][24][25][26][27][28][29], all within + 10% of ideal body weight, participated in the studies. The protocol of this investigation was approved on 5 January 1988 by the Ethical Committee of the Medical Faculty, University of Gottingen.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation